Sams teach yourself C++ in 24 hours - Cadenhead, Rogers; Liberty, Jesse (Sams, 2017)
Sams Teach Yourself C++ in 24 Hours is a hands-on guide to the C++ programming language. Readers are provided with short, practical examples that illustrate key concepts, syntax, and techniques. Using a straightforward approach, this fast and friendly tutorial teaches you everything you need to know, from installing and using a compiler, to debugging the programs you've created, to what's new in C++14. Step-by-step instructions carefully walk you through the most common C++ programming tasks Quizzes and exercises at the end of each chapter help you test yourself to make sure you're ready to go on Learn how to... Install and use a C++ compiler for Windows, Mac OS X, or Linux Build object-oriented programs in C++ Master core C++ concepts such as functions and classes Add rich functionality with templates and lambda expressions Debug your programs for flawless code Learn exception and error-handling techniques Put to use the new features in C++14, the latest version of the language Create and use templates Control program flow with loops Store information in arrays and strings Declare and use pointers Use operator overloading Extend classes with inheritance Use polymorphism and derived classes Employ object-oriented analysis and design.
Includes index. - Description based on online resource; title from title page (Safari, viewed August 25, 2016)
Keywords: C++ (Computer program language); C++ (Langage de programmation); COMPUTERS / Programming Languages / C++